Правова природа договорів, що укладаються в системі громадського харчування - Вусатий, Д. Ю.; Vusatyi, D. Yu. (Вісник Харківського національного університету внутрішніх справ. - 2014. - № 4 (67). - С. 177-184, 2014)
Розглянуто сутність низки цивільно-правових договорів, що укладаються в системі громадського харчування – їдальнях, кафе, ресторанах тощо. Акцентовано увагу на виявленні юридичних особливостей, які дозволяють установити основну мету та видову приналежність указаних договорів до певного договірного типу. Проаналізовано умови та основні елементи цих договорів. Зроблено висновок, що зазначені договори мають подвійне спрямування. Так, одні з них мають своєю метою перенесення права власності на майно. Такі договори запропоновано розглядати як різновиди договору роздрібної купівліпродажу. Інші, котрі своєю метою мають виконання підрядних робіт і передачу їх результату, повинні визнаватися різновидами договору підряду

This article is an attempt to study the legal nature of a number of civil and legal agreements concluded in the system of catering – canteens, cafes and restaurants. This problem is one of not fully researched topics within legal literature on civil law. It is also not unambiguous legal regulation in the domestic law. While studying the legal nature of agreements concluded in the system of catering, the main attention is focuses on detecting such legal features that would allow them to set their main objective and basic species belonging to a particular type of an agreement. Conditions and basic elements of these agreements are the subject of legal analysis. There is an opinion that the form of the agreement can not characterize the legal nature of a civil and legal agreement. As a result of conducted research the author makes a conclusion that stated agreements have dual orientation, in particular, some of them have the objective to transfer the right of ownership on property – these agreements should be viewed as kinds of a contract of retail sale. Others aiming at fulfilling the contract work and transfer of their result should be recognized as a form of a contractor’s agreement. The author supports the point of view as for recognition of contract agreements as mixed ones in case when there is a possibility to provide related services, which do not alter the basic legal nature of contract agreements concluded in system of catering, to the customer together with the works and transfer of their results.

Рассмотрена сущность гражданско-правовых договоров, заключаемых в системе общественного питания – столовых, кафе, ресторанах и т. д. Акцентировано внимание на выявлении юридических особенностей, позволяющих установить основную цель и видовую принадлежность указанных договоров до определенного договорного типа. Проанализированы условия и основные элементы этих договоров. Сделан вывод, что указанные договоры имеют двойное направление. Так, одни из них имеют своей целью перенесение права собственности на имущество. Такие договоры предложено рассматривать как разновидности договора розничной купли-продажи. Другие, имеющие своей целью выполнение подрядных работ и передачу их результата, должны признаваться разновидностями договора подряда.
Legal nature of the agreements concluded in the system of catering
Правовая природа договоров, которые заключаются в системе общественного питания
Keywords: договірні відносини; цивільно-правовий договір; договір роздрібної купівлі-продажу; система громадського харчування; contractual relations; civil and legal agreement; system of catering; contract on a gift certificate; договорные отношения; гражданско-правовой договор; договор розничной купли-продажи; система общественного питания